Islam and new directions in world literature - Bin Tyeer, Sarah R.; Gallien, Claire 1981- (Edinburgh University Press, 2022)
Brings forth the Islamicate as an aesthetic and critical force in World LiteratureDisrupts the one-way traffic in the field of World Literature studies by regarding Islam as both an alternative and a critical force behind creative processes Understands Islam as a driving creative force and situates its contribution in the development, past and present, of world imaginaries Covers a variety of global locations to discuss the Islamicate as developed in Western European, Turkic, Indo-Persian, Middle-Eastern, African, Japanese, Chinese and Philippine literaturesExamines a diversity of genres including fiction and poetry, but also philosophy, oral literature and mangaSince its advent, Islam has been a representational force to be reckoned with, cross-pollinating world literatures in Africa, Europe, Asia, the Pacific Ocean and the Americas. Yet, scholarship on Islam in world literatures has been sparse despite its significant presence. This book understands Islamic literary and cultural heritages as dynamic forces, constantly enriched and enlivened by various humanistic traditions in multiple languages, spanning the lives of individuals and societies throughout history. It is also designed to incorporate a variety of themes, influences, ramifications and representations of Islam in world literatures in classical and contemporary contexts. Exploring Islam's presence in world literatures in two strands: on the one hand, examining the orientalist versions and usages of Islam; and on the other hand, analysing the presence of Islam as Islamicate, this book advances a consideration of Islam as an agent in the history of World Literature